Green intellectual capital: The secret ingredient for organizational competitive advantage in the nursing profession—a cross-sectional study from Egypt - Atalla, Amal Diab Ghanem; Elbassal, Nariman Ahmed Mohamed Mostafa; Kandil‬‏, Faten Shawky; El-Ashry, Ayman Mohamed; Mohamed, Ishraga Abdelgadir Ibrahim; Behilak, Sahar Elsayed Gaber; Elseesy, Naglaa Abdelaziz Mahmoud (Belitung Nursing Journal, 2024)
Background: In the contemporary healthcare environment, managing human resources expertise is just as imperative as having the supreme amount of working capital. Every business must constantly build its capacity, expertise, and competitive edge by utilizing its intellectual property and experience. Objective: This study aimed to assess the relationship between green intellectual capital and organizational competitive advantage among nurses. Methods: The study employed a descriptive correlational design among 350 nurses selected using convenience sampling. Data were collected from March 2023 to June 2023 using the Organizational Competitive Advantage Scale and the Green Intellectual Capital Questionnaire. Data were analyzed using t-test, ANOVA, and Pearson correlation. Results: Most nurses had a moderate level of green intellectual capital (Mean = 3.60, SD = 0.27). The overall mean score for organizational competitive advantage was moderate (Mean = 3.34, SD = 0.34). The overall score of the green intellectual capital (r = 0.257, p <0.001) and its dimensions—green human capital (r = 0.257, p <0.05), green structure capital (r = 0.257, p <0.001), and green relational capital (r = 0.257, p<0.001)—had significant positive correlations with organizational competitive advantage. Conclusion: Being eco-friendly has become a determining factor in the organizational competitive advantage. The study highlights the significance of nursing management in establishing partnerships with external entities to share knowledge and advance sustainable healthcare methods. It advocates for assessing organizational environmental performance and its influence on competitive edge through creating metrics, monitoring progress, and utilizing data for decision-making. Healthcare and nurse administrators are advised to set performance benchmarks, track advancements, and integrate eco-friendly strategies to bolster the hospital’s competitiveness in the market.